Review Influencer Melalui Purchase Intention Terhadap Keputusan Pembelian Produk Skincare di Kabupaten Aceh Barat - Mirna Gandi (Indo Publishing, 2026)
This study aims to examine the effect of influencer reviews on purchasing decisions of skincare products in West Aceh Regency, with purchase intention acting as a mediating variable. A quantitative approach was employed using the proportionate stratified random sampling technique. Data were collected through questionnaires distributed to 100 skincare consumers and analyzed using SmartPLS. The findings reveal that influencer reviews have a positive and significant effect on purchase intention, while purchase intention also positively influences purchasing decisions. Furthermore, influencer reviews indirectly affect purchasing decisions through purchase intention as a mediating factor. These results indicate that the better the quality of influencer reviews, the stronger the consumers’ intention to buy, which ultimately leads to actual purchasing decisions. The study provides practical implications for skincare businesses to carefully select credible influencers in order to enhance marketing effectiveness.